Development of Pop-Up Book Media Social Aspects in Developing Early Children’s Cooperation Capability - Dhiu, Konstantinus Dua; Mere, Veronika Owa (Journal of Nonformal Education, 2025)
This research aims to: (1) produce media in the form of pop-up books to develop social skills in children aged 5-6 years, (2) to determine the level of suitability of pop-up book media for social aspects for children aged 5-6 years. The subjects in this research were children aged 5-6 years at SDK Olabolo One Roof Kindergarten, either in groups or individually. The stages used in this research include Analysis, Design, Development, Implementation and Evaluation. The data collection techniques applied consisted of documentation and distributing questionnaires. The media validation process is carried out through assessments by material experts, learning design experts and learning media experts. The data obtained was analyzed using qualitative and quantitative descriptive approaches. The results of research into the development of pop-up book media are as follows. 1) media expert trials are in the "Very Valid" category with a percentage of 88.57%, 2) learning design expert trials are in the "Valid" category with a percentage of 83.33%, 3) material expert trials are in the "Very Valid" category with a percentage of 92.5%, 4) individual product user trials (children) are in the "Valid" category with a percentage of 85.71% and small group trials are in the "Very Valid" category. with a percentage of 94.44%. Thus, based on the results of testing the pop-up book media by experts and children as product users, it was declared suitable for use with children at SDK Olabolo One Roof Kindergarten. This study is very important to carry out because it provides valuable insight for education managers, especially in Kindergartens, to implement evaluation based on the ADDIE model in order to increase the effectiveness and sustainability of learning design development in Kindergartens which is supported by Pop-Up Book Media to strengthen children’s education in schools.